'Something has to change': A collaborative journey towards academic well-being through critical reflexive practice. Issue 3 (July 2021) - Hurd, Fiona; Singh, Smita
Academic well-being is increasingly being eroded by the ever-shifting demands of the neoliberal university. As stressed early-career research-path academics, we both experienced an acutely depleted sense of well-being within this context. While our struggles were neither unusual nor remarkable, they exposed the difficulties inherent in blending academic work and life outside academia. Through embarking on a process of sharing our experiences with each other, we challenged the traditional silence about stress in academia. We created a shared narrative that interwove a process of writing individual vignettes, longitudinal diarising and critical reflexive questioning. Turning a critical gaze upon our struggles was a powerful means of opening up spaces of self-care within our academic practices. Here, we present the collaborative reflexive process that we used to nurture spaces of well-being in our own academic lives and thus, draw attention to the way reflexive practice can be understood as more than a tool of the researcher, becoming a tool for the researcher. We aim to shift the predominant focus of well-being remedies from being individualised and externally-oriented, to the possibility of collectively developing self-care for well-being within our academic work.